Effects of Education Budget and Enrolment on Science, Technology, Engineering and Mathematics (STEM) Education in Nigeria - AJANI, Mary Oluwatoyin; OJETUNDE, Segun Michael (International Journal of Educational Management, 2021)
In Nigeria, much efforts have been made to improve the status of Science, Technology, Engineering and Mathematics (STEM) education. These revolve around policy uptake and financial commitment. However, the dearth of studies that investigate influence of education budget and enrolment on the development of STEM education created impetus for this study. Expo-facto design that involved collection of time series data on education budget, students’ enrolment and the performance in West African Senior School Certificate Examination (WASSCE) between years 1991-2017 was adopted. Variables in the study were subjected into Auto-Regressive Distribution Lag (ARDL) model. Two structural breaks existed in the development of STEM education in the years under review. These coincided with the adoption and ratification of the Universal Basic Education (UBE) into law in the years 2000 and 2004 respectively. Short run effects of education budget (ß=0.148, t=2.314, p<0.05) and students’ enrolment (ß=-1.153, t=-5.090, p<0.05) had significant effects on the development of STEM while no statistical significant of long run effects was observed. From findings of the study, it is obvious that status of STEM education in Nigeria need to be improved and sustained, therefore, it is recommended that stakeholders in STEM education should show more commitment in terms of facilities provision and funding.